Pengembangan Deteksi Dini dan Asuhan Kebidanan Berkelanjutan terhadap Stunting Menggunakan Artificial Intelegence (AI) Berbasis Web di Desa Bangun Rejo - Siska Suci Triana; Lidya Natalia; Rumondang Sitorus; Isyos Sari; Lamtiar Pasaribu; Lisnawati Laia (Jurnal Pengabdian Bidang Kesehatan, 2025)
The development targets in the Health sector in the 2020–2024 National Medium-Term Development Plan (RPJMN) place one of the main targets for maternal and child health is to reduce the incidence of children under five years old (toddlers) stunting (low height / short) by 30.8% (2018) to 19% in 2024. Optimal Health Status must be prepared since a woman before marriage. Then continued when the woman is pregnant, and while breastfeeding. Childhood is the foundation for growth and development in the next stage, if there are nutritional problems then the consequences that arise are permanent. The risk of stunting by 7x can occur in women 15-49 years who experience anemia and when they become pregnant will be at risk of giving birth to stunted babies. In women of childbearing age aged 15-49 years is the foundation for growth and development in the next stage, if during this period women experience nutritional problems then the consequences that arise can be permanent or irreversible. Its essence is a critical period when a system is plastic and sensitive to its environment, followed by a permanent loss of plasticity and functional capacity (Ummi Kalsum et al., 2021). Before education was provided, most adolescents showed a low level of understanding, namely 31 respondents (56.7%), and awareness of the importance of monitoring nutritional status during adolescence was also minimal. However, after interactive counseling with an easy-to-understand approach, there was a significant increase in knowledge, with 41 respondents (68.3%) showing an increase in understanding, reflected in a change in the knowledge category to a better level. This activity emphasizes the importance of promotive and preventive interventions in areas at high risk of nutritional problems. The implementation of direct and participatory education involving cadres and health workers has proven effective in increasing awareness and forming healthy lifestyle behaviors in adolescents. Therefore, similar education programs need to be implemented continuously to reduce anemia rates to prevent stunting and prevent stunting from adolescence.